Molecular Identification of Potent Antimicrobial Marine Fungi from Manginapudi Beach (Machilipatnam, India) - Shabana, Syed; Satya, Alapati Krishna (International Journal of Membrane Science and Technology, 2023)
The primary objective of this study is to isolate and characterize marine fungi exhibiting antimicrobial properties, collected from Manginapudi Beach located in Machilipatnam along the Indian coast of the Bay of Bengal. The present investigation involved the isolation of marine fungi from seawater samples, with a 0.1 ml sample residue being introduced onto various fungal growth media. These isolated fungi were identified using the Internal Transcribed Spacer (ITS) region. Subsequently, phylogenetic analysis was conducted using MEGA-X to elucidate the relationships between the isolates and closely related species available in the NCBI-GenBank database. The crude extracts of these isolated marine fungi were then prepared and evaluated for their antimicrobial efficacy against various test organisms. Four fungal isolates, namely SS7, SS9, SS10, and SS11, exhibited a 100% similarity match and were conclusively identified as Fusarium incarnatum (SS7), Hamigera insecticola (SS9), Talaromyces tratensis (SS10), and Neurospora crassa (SS11). Notably, this study reports the first-time presence of Acremonium persicinum, Fusarium equiseti, F. incarnatum, F. pernambucanum, Hamigera avellanea, H. insecticola, and Talaromyces tratensis in the Manginapudi Beach region. Among the findings, the ethyl acetate extract of T. tratensis (SS10) demonstrated a significant zone of inhibition, measuring 22.1±0.28 mm against Candida albicans. Similarly, Acremonium persicinum (SS6) exhibited the highest zone of inhibition (29.8±0.26 mm) against Escherichia coli. The outcomes of this study strongly indicate that Manginapudi Beach serves as a valuable repository of marine fungi displaying significant antimicrobial potential. To fully substantiate and utilize this potential, additional investigation is required to isolate and thoroughly characterize the active components within these crude extracts. This in-depth analysis will offer conclusive evidence regarding the bioactive properties of marine fungi.